Bridging academia and communities through higher education extension programs in the Philippines: a meta-synthesis toward theory generation - Angco, Robert Jay N. (Frontiers in Education, 2026)
Higher education institutions (HEIs) catalyze community development through extension programs that promote economic empowerment, skill development, social inclusion, environmental sustainability, and leadership capacity. Despite numerous community extension initiatives in Philippine higher education, a comprehensive synthesis of beneficiary experiences remains absent. This qualitative meta-synthesis systematically reviewed qualitative studies (2021–2024) examining beneficiaries’ lived experiences in Philippine HEI extension programs. Following PRISMA 2020 guidelines, 13 studies meeting Critical Appraisal Skills Program criteria were analyzed using Braun and Clarke’s thematic analysis. Five interconnected themes emerged: (1) Economic Empowerment and Livelihood Enhancement, (2) Skill Development and Capacity Building, (3) Social Inclusion and Community Engagement, (4) Sustainability and Long-Term Impact, and (5) Leadership and Empowerment. These coalesced into an overarching meta-theme: Transformative Community Empowerment through Higher Education Extension Programs. Building upon empowerment theory, community development frameworks, and capability approach, this study proposes the Transformative Community Empowerment Theory (TCET), positing that effective extension programs operate through five interdependent pillars that transform beneficiaries from passive recipients to active change agents. Findings illuminate HEIs’ transformative role in cultivating empowered, self-sustaining communities while strengthening reciprocal HEI-community relationships.